Faculdade de Saúde e Desenvolvimento Humano Santo Agostinho - Beatriz Ferreira Martins; Ana Paula dos Santos Campos; Maycon Rogério Seleghim; Tanimária da Silva Lira Ballani; Erika Okuda Tavares; Magda Lúcia Félix de Oliveira (Universidade Federal do Ceará, 2012)
Accidents caused by snakes should be dealt with attention by public health organs, for these accidents are very frequent and serious. The treatment standardization is indispensable for helping health workers to diagnose and treat the victims. However, sometimes the case clinical evolution presents peculiarities, mainly in accidents with children and elderly people. This study aims at describing and analyzing two clinical cases of accidents with children and snakes of the genera Bothrops spp. and Crotallus spp., which were notified at an information and toxicological assistance center in northwestern Parana (Brazil). We could find some positive aspects in the assistance, such as the precocious access to the health unit, identification of symptoms and antivenom treatment and the lack of antivenom adverse reactions. The negative aspects noticed are the lack of recommended biochemical examinations, for a better diagnosis, as well as an early hospital discharge, disconsidering the possibility of adverse reactions.